Risk management and effective leadership impact on finance and hazard risk mitigation in oil and gas project: case study on a PT. Odira Energy Karang Agung in Indonesia - Ragasa, Reinaldi (2023)
The management project takes a case study in oil and gas industry in Indonesia to analyse how effective leadership affects finance and hazard risks management in oil and gas project. Which leadership traits are important to manage finance and hazard risks are analysed. Furthermore, the research also aims to analyse the source and management plan of these risks. By analysing which important traits are necessary to be an effective leader in managing finance and hazard risks, future leaders can develop these traits so finance and hazard risks can be mitigated to achieve project success.